TEACHING SPEAKING RECOUNT TEXTS TO SENIOR HIGH SCHOOL STUDENTS THROUGH ‘MURDER MYSTERY GAME’ - Fatwatul Hasanah; Desvalini Anwar (Universitas Negeri Padang, 2018)
This paper is aimed at describing the use of ‘Murder Mystery Game’ in teaching speaking recount texts to senior high shchool students. This game is applied to motivate senior high school students to speak English. This game enables students to solve the problem by using the clues given to them. ‘Murder Mystery Game’ allows the students to share ideas to other students by giving some steps to accomplish. Those steps are interviewing character, discussing in group to find the murderer, and discovering the murderer and telling it to the class in form of oral recount texts.